2020
DOI: 10.2478/sues-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Approaches Upon Pension Systems in Central and Eastern European Countries. Triangle Assessment: Free Movement of People, Labor Market and Population Health Features

Abstract: Nowadays, around the world, it can be noticed an important trend towards the pension system reforms. The creation of the European fiscal space, the effects of globalization and the movement of the labour force are important vectors towards creating a new type of social economy. The labour force is constantly moving around the countries that gathered important amounts of capital, especially in industrialized countries. Moreover, the lower levels of the birth rate combined with the increasing level of death rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Our results are consistent with other studies that concluded that a longer working life does not increase the employment rate and neither has a significant effect on the social protection system sustainability [48,49]. On the contrary, a longer working life can induce an increase in unemployment, as was also shown by Jimon et al [50].…”
Section: Resultssupporting
confidence: 93%
“…Our results are consistent with other studies that concluded that a longer working life does not increase the employment rate and neither has a significant effect on the social protection system sustainability [48,49]. On the contrary, a longer working life can induce an increase in unemployment, as was also shown by Jimon et al [50].…”
Section: Resultssupporting
confidence: 93%
“…Balteș et al (2018) state that in order to make the Romanian system sustainable, further reforms are needed. Jimon et al (2020) also highlight that due to the consecutive change of the population structure, it is not enough to analyze the current problems, but future changes should be also considered, and the policy measurements should be forward-looking. Unavoidable and forced tightening of the pension systems all around Europe should be implemented with caution to avoid the decrease of older employees' satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Individual adaptability was proposed as a third type of job performance, in addition to task and contextual performance (M. Griffin et al, 2007;Tucker et al, 2009), and is proving increasingly important (Chen et al, 2020). Facing this, the capacity to adapt will become a de facto competence required from employees at all levels (Jimon et al, 2020). This new reality creates the need to provide both researchers and practitioners with valid instruments to evaluate a person's adaptability.…”
Section: Introductionmentioning
confidence: 99%